2010
DOI: 10.1002/jcop.20374
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence relationship dissolution among couples with children: the counterintuitive role of “Law and Order” neighborhoods

Abstract: This study examined the relationship between intimate partner violence (IPV) relationship dissolution and neighborhood concentrated disadvantage, ethnic heterogeneity, residential instability, collective efficacy, and legal cynicism. Data from the Project on Human Development in Chicago Neighborhoods (PHDCN) Longitudinal survey were used to identify 658 cases of IPV in Wave 1. A generalized boosting model (GBM) was used to determine the best proximal predictors of relationship dissolution from the longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Quite possibly, in socially advantaged neighborhoods, child abuse and neglect remain undetected because residents are less interested in recognizing or reporting it or it may be more likely to be ignored, overlooked, and misconstrued. This is in accordance with a recent study suggesting that neighborhoods willing to control crimes in public spaces (i.e., neighborhoods characterized by low levels of social vulnerability) may have a traditional more “hands off” approach to family violence (Emery, Jolly, & Wu, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Quite possibly, in socially advantaged neighborhoods, child abuse and neglect remain undetected because residents are less interested in recognizing or reporting it or it may be more likely to be ignored, overlooked, and misconstrued. This is in accordance with a recent study suggesting that neighborhoods willing to control crimes in public spaces (i.e., neighborhoods characterized by low levels of social vulnerability) may have a traditional more “hands off” approach to family violence (Emery, Jolly, & Wu, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…24,32,53,54 The lack of institutional resources may also limit the community's ability to implement social order in general. 55 Evidence that violent crime reductions result when communities develop a larger base of positive local institutions (e.g., youth centers), while preventing an influx of negative ones (e.g., bars), supports this possibility. 52 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there has been relatively little work in the past 10 years regarding immigration (even though it has been a major force of social change in the U.S. for ethno-racial compositions and residential mobility) and there are few data available to quantify the impact of immigration status and/or neighborhood immigrant rates on IPV (Emery et al, 2010;Erez & Harper, 2018;Gracia et al, 2014Gracia et al, , 2015Wright & Benson, 2010). The work available has shown mixed results, with some studies suggesting no effect of neighborhood immigration on IPV rates (e.g., Emery et al, 2010;Gracia et al, 2014Gracia et al, , 2015, others suggesting that it might actually prevent or reduce the levels of IPV (Wright & Benson, 2010;Xie et al, 2018), and still others suggesting that the relationship may depend on the gender of the victims (Soller & Kuhlemeier, 2019). The mechanisms underlying the relationship, such as organizational structures, cultural differences in the treatment of IPV, social ties between neighbors, and/or a hesitancy to report this violence, are receiving more attention, but are still poorly understood at this point (Xie & Baumer, 2019).…”
Section: Theoretical Foundations In Social Disorganizationmentioning
confidence: 99%
“…Finally, little research over the past decade has examined the role of community culture and IPV: Emery et al (2010) found that areas with higher levels of legal cynicism (a measure of culture) did, in fact, experience higher levels of IPV relationship dissolution, and Wright and Benson (2010) reported that IPV rates were lower in communities where cultural norms support outside interventions for IPV (i.e., where residents do not believe that IPV is a private matter). This line of research suggests that the type of violence and specificity of norms matter a great deal to the results that are uncovered, but more research is needed on this topic.…”
Section: Developments Over the Past Decadementioning
confidence: 99%
See 1 more Smart Citation